2002
DOI: 10.1128/mcb.22.14.5157-5172.2002
|View full text |Cite|
|
Sign up to set email alerts
|

A Two-Stage, p16INK4A- and p53-Dependent Keratinocyte Senescence Mechanism That Limits Replicative Potential Independent of Telomere Status

Abstract: With increasing frequency during serial passage in culture, primary human keratinocytes express p16 INK4A(p16) and undergo senescence arrest. Keratinocytes engineered to express hTERT maintain long telomeres but typically are not immortalized unless, by mutation or other heritable event, they avoid or greatly reduce p16 expression. We have confirmed that keratinocytes undergo p16-related senescence during growth in culture, whether in the fibroblast feeder cell system or in the specialized K-sfm medium formula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
308
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(331 citation statements)
references
References 69 publications
20
308
1
2
Order By: Relevance
“…Importantly, there was no emergence of a rare, rapidly-growing cell population that would have indicated clonal recovery. Accumulation of p16 has been associated with urothelial senescence in culture and is recognised as an essential block to neoplastic transformation [25]. In agreement with this and observations by Chapman et al [24], we saw a dramatic increase in p16 protein associated with the growth lag around the normal senescence point at passage 12 and growth rate recovery was accompanied by a reduction in p16 expression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, there was no emergence of a rare, rapidly-growing cell population that would have indicated clonal recovery. Accumulation of p16 has been associated with urothelial senescence in culture and is recognised as an essential block to neoplastic transformation [25]. In agreement with this and observations by Chapman et al [24], we saw a dramatic increase in p16 protein associated with the growth lag around the normal senescence point at passage 12 and growth rate recovery was accompanied by a reduction in p16 expression.…”
Section: Discussionsupporting
confidence: 91%
“…We now show that neither loss of p53 nor p16 function had any direct effect on differentiation, in agreement with the normal differentiation potential of keratinocytes with inactivated p16 function [25]. Less expected was the lack of any association between loss of p53 and differentiation, as changes in p53 have been associated with carcinoma in situ [5], thus implying that other changes may contribute to the dysplastic phenotype.…”
Section: Discussionsupporting
confidence: 69%
“…Notch inhibition by DNMAML1 promotes invasive growth of transformed esophageal epithelial cells with EGFR overexpression and p53 dysfunction 68. Moreover, TP53 was frequently mutated in HNSCC cases 6, 7, 53, and the inactivation of p53 plays important role in HNSCC tumorigenesis 43, 69, 70. But it has not been clarified yet whether Notch signaling is closely involved in this.…”
Section: Notch Signaling In Head and Neck Squamous Cell Carcinoma (Hnmentioning
confidence: 99%
“…When grown in co-culture with post-mitotic fibroblast feeder cells, human keratinocytes, exhibit a delay in passage dependent p16 INK4a (p16) expression and have an extended lifespan in culture (Ramirez et al, 2001;Rheinwald et al, 2002;Baek et al, 2003;Fu et al, 2003;Kang et al, 2003;Darbro et al, 2005). We have found that co-culture of keratinocytes with feeder cells delays the accumulation of p16 protein but does not prevent the eventual increase of p16 expression in late passage keratinocytes cultured with feeder cells .…”
Section: Introductionmentioning
confidence: 78%
“…Previous reports that have shown immortalization of cocultured human keratinocytes with TERT alone imply that telomere-dependent mechanisms are the sole barrier preventing continued proliferation in this culture system. However, the presence of inflection points in the growth curves of TERT immortalized keratinocytes co-cultured with feeders (Herbert et al, 2002;Rheinwald et al, 2002;Ramirez et al, 2003), combined with the observations that telomeres experience only limited shortening in co-cultured human keratinocytes (Kang et al, 2004), suggest that telomere-independent mechanisms may still be involved in limiting the replicative capacity of these cells. Thus, examination of p16 expression in TERT-transduced human keratinocytes co-cultured with feeder cells should provide vital information concerning not only the potential safety of telomerase-based cell therapies but also the mechanism of epithelial cell senescence in the co-culture environment.…”
Section: Introductionmentioning
confidence: 99%